2022
DOI: 10.1038/s41586-022-04938-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear chromosome locations dictate segregation error frequencies

Abstract: Chromosome segregation errors during cell divisions generate aneuploidies and micronuclei, which can undergo extensive chromosomal rearrangements such as chromothripsis1–5. Selective pressures then shape distinct aneuploidy and rearrangement patterns—for example, in cancer6,7—but it is unknown whether initial biases in segregation errors and micronucleation exist for particular chromosomes. Using single-cell DNA sequencing8 after an error-prone mitosis in untransformed, diploid cell lines and organoids, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 59 publications
(86 reference statements)
5
52
0
1
Order By: Relevance
“…This is consistent with recent high-resolution live-cell studies in both cancer and non-cancer human cells that showed that the vast majority of lagging chromosomes have a transient nature and are corrected during anaphase by an Aurora-B-dependent mechanism that prevents micronuclei formation, 46,60 and the relatively low frequency of micronuclei formation even after induction of massive chromosome segregation errors by experimental abrogation of the SAC. 61,62 Defects in chromosome alignment are normally avoided by increased Aurora B activity at centromeres of misaligned chromosomes. 27 However, the correction of erroneous attachments underlying some chromosome alignment defects (e.g., syntelic attachments) appears to be less robust in cancer cells that also show overly stabilized kinetochore-microtubule attachments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with recent high-resolution live-cell studies in both cancer and non-cancer human cells that showed that the vast majority of lagging chromosomes have a transient nature and are corrected during anaphase by an Aurora-B-dependent mechanism that prevents micronuclei formation, 46,60 and the relatively low frequency of micronuclei formation even after induction of massive chromosome segregation errors by experimental abrogation of the SAC. 61,62 Defects in chromosome alignment are normally avoided by increased Aurora B activity at centromeres of misaligned chromosomes. 27 However, the correction of erroneous attachments underlying some chromosome alignment defects (e.g., syntelic attachments) appears to be less robust in cancer cells that also show overly stabilized kinetochore-microtubule attachments.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent high-resolution live-cell studies in both cancer and non-cancer human cells that showed that the vast majority of lagging chromosomes have a transient nature and are corrected during anaphase by an Aurora-B-dependent mechanism that prevents micronuclei formation, 46 , 60 and the relatively low frequency of micronuclei formation even after induction of massive chromosome segregation errors by experimental abrogation of the SAC. 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A release from monastrol, an Eg5 kinesin inhibitor, enriched for anaphase lagging of chromosomes 1 and 2 in human cells, chromosome 4 in PtK1 cells, and chromosome 3 + X in Indian Muntjac cells [ 47 , 48 ]. Compromising attachment error correction and the spindle assembly checkpoint (SAC) by inhibiting the kinase Mps1 revealed a high missegregation frequency of larger chromosomes with a difference up to threefold in human cells and of chromosome 3 + X in Indian Muntjac cells [ 33 , 48 , 49 ]. Larger chromosomes were also found to missegregate more frequently in human cells when attachment error correction was compromised by inhibiting Aurora B kinase, when microtubules were stabilized by low concentrations of taxol, or when chromosome congression was compromised by inhibition of the mitotic kinesin CENP-E [ 49 , 50 ].…”
Section: Evidence For Non-random Chromosome Segregation Error Frequen...mentioning
confidence: 99%
“…Compromising attachment error correction and the spindle assembly checkpoint (SAC) by inhibiting the kinase Mps1 revealed a high missegregation frequency of larger chromosomes with a difference up to threefold in human cells and of chromosome 3 + X in Indian Muntjac cells [ 33 , 48 , 49 ]. Larger chromosomes were also found to missegregate more frequently in human cells when attachment error correction was compromised by inhibiting Aurora B kinase, when microtubules were stabilized by low concentrations of taxol, or when chromosome congression was compromised by inhibition of the mitotic kinesin CENP-E [ 49 , 50 ]. Interestingly, generating DNA damage in human cells during the interphase, using ionizing radiation or by causing replication stress, specifically elevated structural rearrangements and micronuclear incorporation of larger chromosomes as well [ 33 , 51 , 52 ].…”
Section: Evidence For Non-random Chromosome Segregation Error Frequen...mentioning
confidence: 99%